Revisiting the Asean way : links to the past, realist interrogations and constructivist responses - Ma.Agnes Alcantara Paculdar (2017)
The Association of Southeast Asian Nations (A SEAN) has been a constant object of scrutiny within the broad analytical and theoretical landscape of international relations. In the face of deep-rooted scholarly preponderance for an analytical frame that privileges the view of international relations as being anarchic, composed of power-seeking and interest maximizing state actors, ASEAN member-states relate with one another in ways that seemingly confound and baffle realist expectations. There exist contending perspectives with regard to its role and capacity as a regional institution, particularly its effectiveness as a security culture, as embodied in the norms that define the ASEAN. This paper argues that the ASEAN has been an institution of vital role in determining the regional order in Southeast Asia primarily because the ASEAN Way has provided an effective framework wherein material circumstances (often a focal point of realist analysis which encompasses the notion of relative differences in state power) and other intra-ASEAN differences, are perceived as not the only important forces shaping the region's approach to dealing with problems and challenges.